Patient Centric Pharmaceutical Drug Product Design-The Impact on Medication Adherence - Enrica Menditto; Valentina Orlando; Giuseppe De Rosa; Paola Minghetti; Umberto Maria Musazzi; Caitriona Cahir; Marta Kurczewska-Michalak; Przemysław Kardas; Elísio Costa; José Manuel Sousa Lobo; Isabel F Almeida (MDPI AG, 2020)
Medication adherence is a growing concern for public health and poor adherence to therapy has been associated with poor health outcomes and higher costs for patients. Interventions for improving adherence need to consider the characteristics of the individual therapeutic regimens according to the needs of the patients. In particular, geriatric and paediatric populations as well as dermatological patients have special needs/preferences that should be considered when designing drug products. Patient Centric Drug Product Pharmaceutical Design (PCDPD) offers the opportunity to meet the needs and preferences of patients. Packaging, orodispersible formulations, fixed dose combinations products, multiparticulate formulations, topical formulations and 3D printing are of particular relevance in a PCDPD process. These will be addressed in this review as well as their impact on medication adherence.